Fruit juice packaging bottle and preparation method thereof
Juice packaging bottles with bio-based composite resin and nano-silver antibacterial coating solve the problems of insufficient antibacterial, antioxidant and environmental protection performance, realize long-term preservation and environmentally friendly production of juice, and are suitable for diversified market needs.
Patent Information
- Application Number
- CN202510814113.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2025-09-12
AI Technical Summary
Existing juice packaging bottles have deficiencies in antibacterial, antioxidant and environmental protection performance, making it difficult to meet the needs of high-quality, green packaging. In addition, bio-based packaging materials are difficult to balance in mechanical properties and processing performance.
The juice packaging bottle is made of bio-based composite resin, including polyethylene terephthalate (PET), polylactic acid (PLA), surface-modified nano-zinc oxide and chitosan quaternary ammonium salt (HACC), combined with low-density polyethylene (LDPE) lining and nano-silver antibacterial coating, through specific preparation processes such as magnetron sputtering and blending technology, to form a juice packaging bottle with excellent anti-corrosion and freshness preservation properties.
It achieves long-term preservation of juice, improves antibacterial ability, reduces the carbon footprint of packaging materials, has good melt fluidity and formability, is suitable for large-scale production, and meets environmental protection and functional requirements.
Smart Images

Figure CN120621859A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging materials, in particular to a juice packaging bottle and a preparation method thereof. Background Art
[0002] As people's living standards improve, the demand for fruit juice drinks is growing, and with it, higher requirements for juice quality and shelf life. As the container that directly contacts the juice, the performance of the packaging bottle plays a key role in its quality and shelf life. Traditional juice bottles are mostly made of a single PET material. While this material offers good transparency and gas barrier properties, it lacks antibacterial, antioxidant, and environmental performance, making it difficult to meet market demand for high-quality, environmentally friendly packaging. Currently, some packaging bottles enhance freshness by adding a single antimicrobial or antioxidant, but this has limited effectiveness. Furthermore, existing bio-based packaging materials struggle to balance mechanical and processing properties, hindering their large-scale application in juice packaging. Therefore, to address these challenges, a juice packaging bottle and its preparation method have been proposed that exhibit excellent antiseptic and freshness-preserving properties, is environmentally friendly, and is easy to process. Summary of the Invention
[0003] The purpose of the present invention is to provide a juice packaging bottle and a preparation method thereof. Through innovative material formula and preparation process, the deficiencies of existing juice packaging bottles in terms of antibacterial, antioxidant, environmental protection and processing performance are solved, the shelf life of juice is extended, and the requirements of the circular economy are met at the same time. In order to achieve the above object, the present invention provides the following technical solutions: The technical solution provided by the present invention is: a juice packaging bottle, the packaging bottle is made of a bio-based composite resin, and the bio-based composite resin comprises, by weight, 60-75 parts of polyethylene terephthalate (PET), 20-30 parts of polylactic acid (PLA), 0.5-1.5 parts of surface-modified nano zinc oxide, and 0.2-0.6 parts of chitosan quaternary ammonium salt (HACC); the inner wall of the bottle mouth of the packaging bottle is provided with a low-density polyethylene (LDPE) lining and a nano-silver antibacterial coating, the thickness of the LDPE lining is 0.15-0.25 mm, and the thickness of the nano-silver antibacterial coating is 0.05-0.1 mm.
[0004] Furthermore, the particle size of the surface-modified nano-zinc oxide is 15-30nm, the surface is modified by the silane coupling agent KH550, and the dispersion uniformity in the bio-based composite resin is ≥95%; the quaternization degree of chitosan quaternary ammonium salt is 70%-85%, the molecular weight is 30-50kDa, and chemical bonds are formed with the bio-based composite resin through in situ grafting technology. Furthermore, the nanosilver antibacterial coating was prepared by a magnetron sputtering process, the average particle size of the silver particles in the coating was 5-10 nm, and the coating thickness uniformity error was ≤±5%. A method for preparing a juice packaging bottle comprises the following steps: S1: Polyethylene terephthalate, polylactic acid, surface-modified nano-zinc oxide and chitosan quaternary ammonium salt are put into a twin-screw extruder in proportion, melt-blended at a temperature of 240-260°C and a screw speed of 300-400 r / min, and extruded into granules to obtain a bio-based composite resin; S2: The bio-based composite resin pellets are fed into an injection molding machine and molded into a hollow tubular preform with a wall thickness of 2.0-2.5 mm at a melt temperature of 260-280°C and an injection pressure of 80-100 MPa; S3: After the preform is heated to 110-130℃ and softened, it is blown into a bottle body using 1.5-2.0MPa high-pressure air, and an LDPE lining is injection-molded on the inner wall of the bottle mouth. S4: The inner wall of the bottle mouth after injection molding is subjected to magnetron sputtering treatment to deposit a nano-silver antibacterial coating on the surface of the LDPE liner. The sputtering power is 100-150W, the argon flow rate is 20-30sccm, and the deposition time is 5-8min. S5: The formed packaging bottles are sterilized by ultraviolet light, and then tested for sealing, compressive strength and additive migration in sequence. The bottles are put into storage after passing the tests. Furthermore, the preparation method of the surface-modified nano-zinc oxide in S1 is as follows: adding nano-zinc oxide to an ethanol solution, adding a silane coupling agent KH550, dispersing the solution under an ultrasonic power of 200-300 W for 30-60 minutes, and drying to obtain the surface-modified nano-zinc oxide.
[0005] Furthermore, the injection molding temperature for depositing the nanosilver antibacterial coating on the surface of the LDPE liner in S4 is 180-200°C, and the injection molding pressure is 50-70 MPa; Furthermore, the sealing test of S5 adopts the pressure difference method, maintaining the pressure at 20kPa for 30s, and the pressure drop value is ≤5kPa; the additive migration amount is detected by high performance liquid chromatography, and the detection conditions are: chromatographic column C18 (4.6mm×250mm, 5μm), mobile phase methanol-water (volume ratio 60:40), flow rate 1.0mL / min, and detection wavelength 254nm.
[0006] The beneficial effects of this technical solution are: (1) The synergistic effect of surface-modified nano zinc oxide and chitosan quaternary ammonium salt (HACC) in the bio-based composite resin gives the packaging bottle a strong antibacterial ability, which can effectively inhibit the growth of common microorganisms in juice; at the same time, nano zinc oxide also has a good ultraviolet shielding effect, and combined with the barrier properties of PET and PLA, it can reduce the oxidation and decomposition of nutrients in juice and extend the shelf life of juice. (2) The bio-based composite resin blended with PET and PLA can reduce the carbon footprint of packaging materials compared to traditional all-PET packaging bottles. The biodegradable properties of PLA help reduce environmental pollution and are in line with the development trend of green packaging. (3) By optimizing the raw material ratio and preparation process parameters, the bio-based composite resin has good melt fluidity and moldability, and can be mass-produced through existing injection-blow molding equipment, reducing production costs; The LDPE lining and nano-silver antibacterial coating at the bottle mouth form double protection, which not only improves the sealing of the bottle mouth and reduces the entry of oxygen and moisture, but the nano-silver antibacterial coating can also continuously inhibit the growth of microorganisms in the bottle mouth area, further ensuring the quality and safety of the juice. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 This is a flowchart of the steps of a juice packaging bottle and a preparation method thereof proposed by the present invention; Figure 2 This is a table showing the difference in raw material ratios for a juice packaging bottle and a preparation method thereof proposed in the present invention; Figure 3 This is a table of material parameter differences for a juice packaging bottle and a preparation method thereof proposed in the present invention; Figure 4 The bottle mouth structure parameters of a juice packaging bottle and its preparation method proposed in the present invention; Figure 5 This is a performance test table of a juice packaging bottle and its preparation method proposed in the present invention; Figure 6 This is a table of preparation process parameters for a juice packaging bottle and a preparation method thereof proposed in the present invention; Figure 7 This is a comparison table of data parameter differences of various embodiments of a juice packaging bottle and a preparation method thereof proposed in the present invention. DETAILED DESCRIPTION
[0008] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0009] The specific implementation process is as follows: Example 1: See also Figure 1-7 The present invention provides a technical solution: a juice packaging bottle and a preparation method thereof, comprising a bio-based composite resin comprising, by weight, 65 parts of polyethylene terephthalate (PET), 25 parts of polylactic acid (PLA), 1 part of surface-modified nano-zinc oxide, and 0.5 parts of chitosan quaternary ammonium salt (HACC); wherein the surface-modified nano-zinc oxide has a particle size of 20 nm and is surface-modified with a silane coupling agent KH550; the chitosan quaternary ammonium salt has a quaternization degree of 75% and a molecular weight of 40 kDa; the low-density polyethylene (LDPE) lining on the inner wall of the bottle mouth has a thickness of 0.2 mm, and the nano-silver antibacterial coating has a thickness of 0.08 mm; The preparation process is as follows: S1: Preparation of surface-modified nano-zinc oxide: 10 g of nano-zinc oxide with a particle size of 20 nm was added to 100 mL of ethanol solution, 1 g of silane coupling agent KH550 was added, and the mixture was dispersed at 200 W ultrasonic power for 30 min, and then dried at 60°C for 12 h to obtain surface-modified nano-zinc oxide; S2: Preparation of bio-based composite resin: 650 g of polyethylene terephthalate, 250 g of polylactic acid, 10 g of the surface-modified nano-zinc oxide prepared above, and 5 g of chitosan quaternary ammonium salt were weighed and put into a twin-screw extruder. The mixture was melt-blended at a temperature of 250° C. and a screw speed of 350 r / min, and extruded and granulated to obtain a bio-based composite resin; S3: Bottle preform preparation: The bio-based composite resin pellets are fed into an injection molding machine and molded into a hollow tubular bottle preform with a wall thickness of 2.2 mm at a melt temperature of 270°C and an injection pressure of 90 MPa; S4: Blow molding and bottle mouth treatment: After the preform is heated to 120°C and softened, it is blown into the bottle body using 1.8MPa high-pressure air. At the same time, a 0.2mm thick LDPE liner is injection molded on the inner wall of the bottle mouth. The inner wall of the injection-molded bottle mouth is treated with magnetron sputtering to deposit a nano-silver antibacterial coating on the surface of the LDPE liner. The sputtering power is 120W, the argon flow rate is 25sccm, and the deposition time is 6min. S5: Post-processing: The formed bottles are sterilized with UV light and tested for sealing using the differential pressure method, maintaining the pressure at 20kPa for 30 seconds with a pressure drop of 3kPa. High-performance liquid chromatography is used to test the migration of additives. If the test results meet food safety standards, the bottles are qualified for storage. The packaging bottle prepared in this example, thanks to the rational ratio of PET and PLA, balances mechanical properties with environmental characteristics. The synergistic effect of surface-modified nano-zinc oxide and HACC makes the bottle's antibacterial rate against Escherichia coli and Staphylococcus aureus reach 99.2%, effectively inhibiting the growth of microorganisms in juice. The LDPE lining and nano-silver antibacterial coating at the bottle mouth form a double-sealed antibacterial structure, reducing oxygen permeability by 35% compared to traditional PET bottles, significantly extending the shelf life of juice. Furthermore, the addition of PLA reduces the carbon footprint of the bottle by 22% compared to traditional PET packaging, in line with the concept of green packaging. Example 1 achieves a balanced improvement in antibacterial, freshness-preserving, and environmental performance while ensuring the basic performance of the packaging bottle by optimizing the raw material ratio and process parameters; its successful preparation verifies the feasibility of the material formula and preparation process in the claims, especially the preparation method of surface-modified nano-zinc oxide and the application of magnetron sputtering technology in the preparation of antibacterial coatings, providing a basic process reference for subsequent examples; at the same time, the performance test results of this example show that under this parameter combination, the packaging bottle can meet the actual needs of juice packaging and has good potential for industrial production.
[0010] Example 2: See also Figure 1-7 The present invention provides a technical solution: a juice packaging bottle and a preparation method thereof, comprising a bio-based composite resin comprising, by weight, 70 parts of polyethylene terephthalate (PET), 20 parts of polylactic acid (PLA), 1.5 parts of surface-modified nano-zinc oxide, and 0.3 parts of chitosan quaternary ammonium salt (HACC); the surface-modified nano-zinc oxide has a particle size of 15 nm and is modified with a silane coupling agent KH550; the chitosan quaternary ammonium salt has a quaternization degree of 80% and a molecular weight of 35 kDa; the LDPE lining of the bottle mouth has a thickness of 0.18 mm, and the nano-silver antibacterial coating has a thickness of 0.07 mm; The preparation process is as follows: S1: Preparation of surface-modified nano-zinc oxide: 15 g of nano-zinc oxide with a particle size of 15 nm was added to 150 mL of ethanol solution, 1.5 g of silane coupling agent KH550 was added, and the mixture was dispersed at 250 W ultrasonic power for 40 min, and then dried at 65°C for 10 h to obtain surface-modified nano-zinc oxide; S2: Preparation of bio-based composite resin: 700 g of polyethylene terephthalate, 200 g of polylactic acid, 15 g of the surface-modified nano-zinc oxide prepared above, and 3 g of chitosan quaternary ammonium salt were weighed and put into a twin-screw extruder. The mixture was melt-blended at a temperature of 245° C. and a screw speed of 300 r / min, and extruded and granulated to obtain a bio-based composite resin; S3: Bottle preform preparation: The bio-based composite resin pellets are fed into an injection molding machine and molded into a hollow tubular bottle preform with a wall thickness of 2.0 mm at a melt temperature of 265°C and an injection pressure of 85 MPa; S4: Blow molding and bottle mouth treatment: After the preform is heated to 115°C to soften it, it is blown into the bottle body using 1.6MPa high-pressure air. At the same time, a 0.18mm thick LDPE liner is injection molded on the inner wall of the bottle mouth. The inner wall of the injection-molded bottle mouth is treated with magnetron sputtering to deposit a nano-silver antibacterial coating on the surface of the LDPE liner. The sputtering power is 110W, the argon flow rate is 22sccm, and the deposition time is 5min. S5: Post-processing: The formed bottles are sterilized with UV light. The sealing test pressure drop value is 2kPa. The additive migration test is qualified and the bottles are put into storage. The high proportion of PET imparts excellent mechanical strength to the bottle, achieving a tensile strength of 52 MPa, making it resistant to damage during transportation and storage. The high addition level (1.5%) of surface-modified nano-zinc oxide and the optimized dispersion process ensure 96% uniformity in the resin. Combined with HACC, this achieves a 99.5% antibacterial rate, significantly improving the long-lasting antibacterial properties. Adjustments to the bottle neck coating process parameters ensure a tighter bond between the nano-silver antibacterial coating and the LDPE liner, resulting in an oxygen transmission rate as low as 1.8cc / m²·day, further enhancing the bottle's freshness preservation. Example 2 highlights the mechanical properties and antibacterial durability of the packaging bottle by increasing the PET ratio and optimizing the addition amount of nano-zinc oxide and process parameters. The results show that under specific process conditions, the key performance indicators of the packaging bottle can be further improved. However, the reduction in the PLA ratio leads to its relatively slow biodegradation rate. In terms of the balance between environmental performance and mechanical properties, it provides a comparative reference for subsequent examples and proves that the present technical solution can achieve targeted optimization of performance through parameter adjustment.
[0011] Embodiment three: See also Figure 1-7The present invention provides a technical solution: a juice packaging bottle and a preparation method thereof, comprising a bio-based composite resin comprising, by weight, 60 parts of polyethylene terephthalate (PET), 30 parts of polylactic acid (PLA), 0.8 parts of surface-modified nano-zinc oxide, and 0.6 parts of chitosan quaternary ammonium salt (HACC); the surface-modified nano-zinc oxide has a particle size of 30 nm and is modified with a silane coupling agent KH550; the chitosan quaternary ammonium salt has a quaternization degree of 70% and a molecular weight of 50 kDa; the bottle mouth has an LDPE lining with a thickness of 0.25 mm and a nano-silver antibacterial coating with a thickness of 0.1 mm; The preparation process is as follows: S1: Preparation of surface-modified nano-zinc oxide: 8 g of nano-zinc oxide with a particle size of 30 nm was added to 80 mL of ethanol solution, 0.8 g of silane coupling agent KH550 was added, and the mixture was dispersed at 300 W ultrasonic power for 50 min, and then dried at 70°C for 8 h to obtain surface-modified nano-zinc oxide; S2: Preparation of bio-based composite resin: 600 g of polyethylene terephthalate, 300 g of polylactic acid, 8 g of the surface-modified nano-zinc oxide prepared above, and 6 g of chitosan quaternary ammonium salt were weighed and put into a twin-screw extruder. The mixture was melt-blended at a temperature of 260° C. and a screw speed of 400 r / min, and extruded and granulated to obtain a bio-based composite resin; S3: Bottle preform preparation: The bio-based composite resin pellets are put into an injection molding machine and molded into a hollow tubular bottle preform with a wall thickness of 2.5 mm at a melt temperature of 280°C and an injection pressure of 100 MPa; S4: Blow molding and bottle mouth treatment: After the preform is heated to 130°C and softened, it is blown into the bottle body using 2.0MPa high-pressure air. At the same time, a 0.25mm thick LDPE liner is injection molded on the inner wall of the bottle mouth. The inner wall of the injection-molded bottle mouth is treated with magnetron sputtering to deposit a nano-silver antibacterial coating on the surface of the LDPE liner. The sputtering power is 150W, the argon flow rate is 30sccm, and the deposition time is 8min. S5: Post-processing: After the packaging bottles are treated with UV sterilization, the sealing test and the additive migration test are qualified, meeting the warehousing standards; The high proportion of PLA shortens the bottle's degradation cycle in a composting environment to 14-17 months, demonstrating outstanding environmental performance. The large amount of HACC (0.6%) added synergistically with nano-zinc oxide achieves an antibacterial rate of up to 99.8%, effectively inhibiting common microorganisms in juice. While higher blow molding pressures and temperatures improve production efficiency, they also lead to uneven stress distribution within the bottle, reducing tensile strength to 45 MPa. Nevertheless, the overall performance still meets the basic requirements for juice packaging, with excellent antibacterial and environmental performance. Example 3 highlights the environmental and antibacterial properties of the packaging bottle. By significantly increasing the PLA ratio and HACC dosage, the feasibility of this technical solution in enhancing environmental protection and antibacterial functions is verified. Although the mechanical properties are affected to a certain extent, it proves that the raw material formula can be adjusted to meet specific market needs. For example, for organic juice products with extremely high environmental requirements, the packaging bottle of this example has strong applicability, demonstrating the flexibility and diversity of this technical solution.
[0012] Example 4: See also Figure 1-7 The present invention provides a technical solution: a juice packaging bottle and a preparation method thereof, comprising a bio-based composite resin comprising, by weight, 68 parts of polyethylene terephthalate (PET), 22 parts of polylactic acid (PLA), 1.2 parts of surface-modified nano-zinc oxide, and 0.4 parts of chitosan quaternary ammonium salt (HACC); the surface-modified nano-zinc oxide has a particle size of 22 nm and is modified with a silane coupling agent KH550; the chitosan quaternary ammonium salt has a quaternization degree of 82% and a molecular weight of 38 kDa; the bottle mouth has an LDPE lining with a thickness of 0.22 mm and a nano-silver antibacterial coating with a thickness of 0.09 mm; The preparation process is as follows: S1: Preparation of surface-modified nano-zinc oxide: 12 g of nano-zinc oxide with a particle size of 22 nm was added to 120 mL of ethanol solution, 1.2 g of silane coupling agent KH550 was added, and the mixture was dispersed at 220 W ultrasonic power for 35 min, and then dried at 62°C for 11 h to obtain surface-modified nano-zinc oxide; S2: Preparation of bio-based composite resin: 680 g of polyethylene terephthalate, 220 g of polylactic acid, 12 g of the surface-modified nano-zinc oxide prepared above, and 4 g of chitosan quaternary ammonium salt were weighed and put into a twin-screw extruder. The mixture was melt-blended at a temperature of 255° C. and a screw speed of 380 r / min, and extruded and granulated to obtain a bio-based composite resin; S3: Bottle preform preparation: The bio-based composite resin pellets are fed into an injection molding machine and molded into a hollow tubular bottle preform with a wall thickness of 2.3 mm at a melt temperature of 275°C and an injection pressure of 95 MPa; S4: Blow molding and bottle mouth treatment: After the preform is heated to 125°C and softened, it is blown into the bottle body using 1.9MPa high-pressure air. At the same time, a 0.22mm thick LDPE liner is injection molded on the inner wall of the bottle mouth. The inner wall of the injection-molded bottle mouth is treated with magnetron sputtering to deposit a nano-silver antibacterial coating on the surface of the LDPE liner. The sputtering power is 130W, the argon flow rate is 28sccm, and the deposition time is 7min. S5: Post-processing: After testing, the sealing and additive migration of the packaging bottles meet the requirements and can be put into storage; The packaging bottle prepared in this example achieves a good balance between mechanical properties and antibacterial properties, with a tensile strength of 50 MPa and an antibacterial rate of 99.3%. The optimized nano-zinc oxide addition amount and dispersion process ensure its uniform dispersion in the resin, effectively exerting its UV shielding and antibacterial effects. The light stability of the packaging bottle is significantly improved. Under light conditions, the retention rate of vitamin C in the juice is 42% higher than that of traditional PET bottles. The sealed antibacterial structure of the bottle mouth keeps the oxygen permeability at a low level, further ensuring the quality of the juice. Example 4 achieves a synergistic improvement in multiple performance properties of the packaging bottle by fine-tuning the raw material ratios and process parameters; the results show that within the parameter range of this technical solution, through reasonable optimization, a juice packaging bottle with excellent comprehensive performance can be prepared; in particular, the improvement in light stability provides an effective solution for packaging light-sensitive juice products, reflecting the advantages of this technical solution in meeting the packaging needs of different juice products and having important practical application value.
[0013] Embodiment 5: See also Figure 1-7 The present invention provides a technical solution: a juice packaging bottle and a preparation method thereof, comprising a bio-based composite resin comprising, by weight, 62 parts of polyethylene terephthalate (PET), 28 parts of polylactic acid (PLA), 0.5 parts of surface-modified nano-zinc oxide, and 0.3 parts of chitosan quaternary ammonium salt (HACC); wherein the surface-modified nano-zinc oxide has a particle size of 18 nm and is surface-modified with a silane coupling agent KH550; the chitosan quaternary ammonium salt has a quaternization degree of 78% and a molecular weight of 45 kDa; the low-density polyethylene (LDPE) lining on the inner wall of the bottle mouth has a thickness of 0.15 mm, and the nano-silver antibacterial coating has a thickness of 0.05 mm; The preparation process is as follows: S1: Preparation of surface-modified nano-zinc oxide: 5 g of nano-zinc oxide with a particle size of 18 nm was added to 50 mL of ethanol solution, and 0.5 g of silane coupling agent KH550 was added. The mixture was dispersed under an ultrasonic power of 280 W for 45 min and then dried at 68°C for 9 h to obtain surface-modified nano-zinc oxide. S2: Preparation of bio-based composite resin: 620 g of polyethylene terephthalate, 280 g of polylactic acid, 5 g of the surface-modified nano-zinc oxide prepared above, and 3 g of chitosan quaternary ammonium salt were weighed and put into a twin-screw extruder. The mixture was melt-blended at a temperature of 248°C and a screw speed of 320 r / min, and extruded and granulated to obtain a bio-based composite resin; S3: Bottle preform preparation: The bio-based composite resin pellets are placed in an injection molding machine and molded into a hollow tubular bottle preform with a wall thickness of 2.1 mm at a melt temperature of 268°C and an injection pressure of 88 MPa; S4: Blow molding and bottle mouth treatment: After the preform is heated to 118°C and softened, it is blown into the bottle body using 1.7MPa high-pressure air. At the same time, a 0.15mm thick LDPE liner is injection molded on the inner wall of the bottle mouth. The inner wall of the injection-molded bottle mouth is treated with magnetron sputtering to deposit a nano-silver antibacterial coating on the surface of the LDPE liner. The sputtering power is 105W, the argon flow rate is 20sccm, and the deposition time is 5min. S5: Post-processing: The formed bottles are sterilized with UV light and tested for sealing using the differential pressure method, maintaining the pressure at 20kPa for 30 seconds with a pressure drop of 4kPa. High-performance liquid chromatography is used to test the migration of additives. If the test results meet food safety standards, the bottles are qualified for storage. In this embodiment, the high proportion of PLA makes the packaging bottle have outstanding biodegradability. In a simulated composting environment, the weight loss rate reached 18% within 3 months. Although the addition amount of surface-modified nano-zinc oxide and HACC is relatively low, the synergistic effect of the two still achieves an antibacterial rate of 98.8% against Escherichia coli and Staphylococcus aureus. The LDPE lining and nano-silver antibacterial coating at the bottle mouth form a sealed antibacterial structure, and the oxygen permeability is reduced by 30% compared with traditional PET bottles. At the same time, the ratio of PET to PLA gives the packaging bottle good toughness, with an impact strength of 25kJ / m², making it less susceptible to damage during transportation, and taking into account both environmental performance and practical performance.
[0014] Example 6: See also Figure 1-7 The present invention provides a technical solution: a juice packaging bottle and a preparation method thereof, comprising a bio-based composite resin comprising, by weight, 75 parts of polyethylene terephthalate (PET), 20 parts of polylactic acid (PLA), 1.3 parts of surface-modified nano-zinc oxide, and 0.2 parts of chitosan quaternary ammonium salt (HACC); wherein the surface-modified nano-zinc oxide has a particle size of 28 nm and is surface-modified with a silane coupling agent KH550; the chitosan quaternary ammonium salt has a quaternization degree of 85% and a molecular weight of 32 kDa; the low-density polyethylene (LDPE) lining on the inner wall of the bottle mouth has a thickness of 0.25 mm, and the nano-silver antibacterial coating has a thickness of 0.1 mm; The preparation process is as follows: S1: Preparation of surface-modified nano-zinc oxide: 13 g of nano-zinc oxide with a particle size of 28 nm was added to 130 mL of ethanol solution, and 1.3 g of silane coupling agent KH550 was added. The mixture was dispersed under an ultrasonic power of 240 W for 42 min, and then dried at 63°C for 10.5 h to obtain surface-modified nano-zinc oxide. S2: Preparation of bio-based composite resin: 750 g of polyethylene terephthalate, 200 g of polylactic acid, 13 g of the surface-modified nano-zinc oxide prepared above, and 2 g of chitosan quaternary ammonium salt were weighed and put into a twin-screw extruder. The mixture was melt-blended at a temperature of 252° C. and a screw speed of 360 r / min, and extruded and granulated to obtain a bio-based composite resin; S3: Bottle preform preparation: The bio-based composite resin pellets are fed into an injection molding machine and molded into a hollow tubular bottle preform with a wall thickness of 2.0 mm at a melt temperature of 262°C and an injection pressure of 82 MPa; S4: Blow molding and bottle mouth treatment: After the preform is heated to 112°C and softened, it is blown into the bottle body using 1.5MPa high-pressure air. At the same time, a 0.25mm thick LDPE liner is injection molded on the inner wall of the bottle mouth. The inner wall of the injection-molded bottle mouth is treated with magnetron sputtering to deposit a nano-silver antibacterial coating on the surface of the LDPE liner. The sputtering power is 140W, the argon flow rate is 28sccm, and the deposition time is 7min. S5: Post-processing: The formed bottles are sterilized with UV light and tested for sealing using the differential pressure method, maintaining the pressure at 20kPa for 30 seconds with a pressure drop of 2kPa. High-performance liquid chromatography is used to test the migration of additives. If the test results meet food safety standards, the bottles are qualified for storage. In this example, the high proportion of PET imparts exceptional mechanical strength to the bottle, achieving a tensile strength of 55 MPa, making it suitable for long-distance transportation and stacked storage. The synergistic effect of surface-modified nano-zinc oxide (1.3%) and highly quaternized HACC (HACC) achieves an antibacterial rate of 99.6%, effectively inhibiting microbial contamination of the juice. The thicker LDPE lining and nano-silver antibacterial coating further enhance the sealing and antibacterial properties of the bottle opening, resulting in an oxygen permeability as low as 1.5 cc / m² / day, significantly extending the shelf life of the juice. Despite the relatively low proportion of PLA, the bottle's carbon footprint is still reduced to a certain extent, achieving a good balance between performance and environmental protection.
[0015] See also Figure 1-7From the perspective of raw material ratios, the changes in the proportions of PET and PLA in the six examples significantly affect the basic performance of the packaging bottles; in Example 1, PET accounts for 65 parts and PLA accounts for 25 parts. While ensuring certain mechanical properties, PLA gives it better environmental potential; while in Example 6, the PET ratio is increased to 75 parts, the tensile strength reaches the highest 55MPa, enhancing the pressure-bearing capacity of the packaging bottle, but the PLA ratio is reduced to 20 parts, which weakens the biodegradability to a certain extent; the addition amount and characteristic differences of surface-modified nano-zinc oxide and chitosan quaternary ammonium salt (HACC) directly determine the antibacterial and fresh-keeping capabilities of the packaging bottle; for example, in Example 3, the HACC addition amount is 0.6 parts, combined with 0.8 parts of nano-zinc oxide, the antibacterial rate is as high as 99.8%; while in Example 5, the addition amounts of both are relatively low, the antibacterial rate is 98.8%, but the biodegradation weight loss rate reaches 18% after 3 months, with outstanding environmental advantages. In terms of material parameters, the particle size of nano-zinc oxide and the degree of quaternization and molecular weight of HACC affect its dispersibility and antibacterial activity in the resin. Example 2 uses 15nm nano-zinc oxide. Its small particle size results in a large specific surface area and good dispersion uniformity. When combined with HACC with a degree of quaternization of 80% and a molecular weight of 35kDa, the antibacterial rate reaches 99.5%. Although the 30nm nano-zinc oxide in Example 3 has a larger particle size, a high antibacterial rate is still achieved by increasing the amount of HACC added and adjusting the process. These data indicate that the raw material ratio and material parameters need to be coordinated to achieve a balance between mechanical properties, antibacterial properties, and environmental performance to meet the packaging requirements of different juice products. In the blending process, temperature and screw speed affect the mixing uniformity and molecular structure of the bio-based composite resin; Example 3 uses a blending temperature of 260°C and a screw speed of 400 r / min. The higher temperature and speed promote the full fusion of the components, but may also cause decomposition of some components; while Example 2 uses the parameters of 245°C and 300 r / min for blending. The relatively mild conditions help reduce the loss of raw material performance, but the mixing uniformity needs to be ensured by extending the time; the temperature and pressure parameters of the injection molding and blow molding processes directly determine the molding accuracy and mechanical properties of the bottle preform and bottle body; Example 6 can still mold a bottle body with high tensile strength at a lower injection temperature of 262°C and an injection pressure of 82 MPa, indicating that the raw material formula and process parameters are well adapted; although Example 3 increases the injection temperature and pressure, the high proportion of PLA leads to uneven internal stress distribution and the tensile strength drops to 45 MPa. In Example 3, a sputtering power of 150 W, an argon flow rate of 30 sccm, and a deposition time of 8 minutes were used to prepare a relatively thick coating (0.1 mm) with excellent antibacterial properties. In Example 5, the magnetron sputtering parameters were relatively low, the coating thickness was only 0.05 mm, and the antibacterial properties were relatively weak. This shows that the preparation process parameters need to be precisely controlled according to the characteristics of the raw materials and the expected performance. Improper parameters in any link may affect the overall quality of the packaging bottle. A reasonable combination of process parameters is an important guarantee for achieving high performance of the packaging bottle. Market Application and Prospects Comparing the comprehensive performance of the six bottles in the examples reveals diverse performance advantages under different parameter combinations, making them suitable for different market demands. In terms of antimicrobial performance, Example 3, thanks to its high HACC ratio and optimized process, achieves an antimicrobial rate of 99.8%, making it suitable for high-end juice products with extremely high microbial control requirements. Although Example 5 has an antimicrobial rate of 98.8%, its biodegradation weight loss rate reaches 18% after 3 months, making it competitive in the environmentally conscious market. Oxygen permeability and vitamin C retention rate reflect the bottle's ability to preserve freshness. Example 6 has an oxygen permeability as low as 1.5cc / m²·day, which can effectively delay juice oxidation. Example 4, through the rational combination of raw materials and process, increases vitamin C retention by 42%, making it suitable for juice categories with high nutritional requirements. In terms of mechanical properties, Example 6 has a tensile strength of 55 MPa, making it suitable for long-distance transportation and stacked storage. Example 5 has an impact strength of 25 kJ / m², which can better protect the contents in collision-prone environments. These performance differences demonstrate the high flexibility of the packaging bottle preparation scheme of the present invention. Manufacturers can adjust the raw material ratio and preparation process parameters according to the characteristics of the juice product (such as shelf life requirements, sales channels, and target consumer groups) to customize packaging bottles to meet specific needs. This not only improves product quality but also meets the diverse environmental and functional requirements of the market, thus gaining a competitive advantage for the company.
[0016] The above description is merely an embodiment of the present invention. Common knowledge such as the specific technical solutions or features of the solutions is not described in detail herein. It should be noted that those skilled in the art may make several modifications and improvements without departing from the technical solution of the present invention. These modifications and improvements should also be considered as within the scope of protection of the present invention and will not affect the effectiveness of the implementation of the present invention or the practical application of the patent. The scope of protection claimed in this application shall be based on the content of the claims, and the specific implementation methods and other records in the specification may be used to interpret the content of the claims.
Claims
1. A juice packaging bottle, characterized by: The packaging bottle is made of a bio-based composite resin, which comprises, by weight, 60-75 parts of polyethylene terephthalate (PET), 20-30 parts of polylactic acid (PLA), 0.5-1.5 parts of surface-modified nano zinc oxide, and 0.2-0.6 parts of chitosan quaternary ammonium salt (HACC). The inner wall of the bottle mouth of the packaging bottle is provided with a low-density polyethylene (LDPE) lining and a nano-silver antibacterial coating, the thickness of the LDPE lining is 0.15-0.25 mm, and the thickness of the nano-silver antibacterial coating is 0.05-0.1 mm.
2. The juice packaging bottle according to claim 1, characterized in that: The particle size of the surface-modified nano-zinc oxide is 15-30 nm, the surface is modified by silane coupling agent KH550, and the dispersion uniformity in the bio-based composite resin is ≥95%; the quaternization degree of the chitosan quaternary ammonium salt is 70%-85%, the molecular weight is 30-50 kDa, and chemical bonding is formed with the bio-based composite resin through in-situ grafting technology.
3. The juice packaging bottle according to claim 1 or 2, characterized in that: The nano silver antibacterial coating is prepared by a magnetron sputtering process, the average particle size of the silver particles in the coating is 5-10 nm, and the coating thickness uniformity error is ≤±5%.
4. A method for preparing a juice packaging bottle according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Polyethylene terephthalate, polylactic acid, surface-modified nano-zinc oxide and chitosan quaternary ammonium salt are put into a twin-screw extruder in proportion, melt-blended at a temperature of 240-260°C and a screw speed of 300-400 r / min, and extruded into granules to obtain a bio-based composite resin; S2: putting the bio-based composite resin particles into an injection molding machine, and molding them into a hollow tubular bottle preform with a wall thickness of 2.0-2.5 mm at a melting temperature of 260-280° C. and an injection pressure of 80-100 MPa; S3: After the preform is heated to 110-130℃ and softened, it is blown into a bottle body using 1.5-2.0MPa high-pressure air, and an LDPE lining is injection-molded on the inner wall of the bottle mouth. S4: The inner wall of the bottle mouth after injection molding is subjected to magnetron sputtering treatment to deposit a nano-silver antibacterial coating on the surface of the LDPE liner. The sputtering power is 100-150W, the argon flow rate is 20-30sccm, and the deposition time is 5-8min. S5: The formed packaging bottles are sterilized by ultraviolet light, and then tested for sealing, compressive strength and additive migration in sequence. The bottles are put into storage after passing the tests.
5. The method for preparing a juice packaging bottle according to claim 4, characterized in that: The preparation method of the surface-modified nano zinc oxide described in S1 is as follows: adding nano zinc oxide to an ethanol solution, adding a silane coupling agent KH550, dispersing the solution under an ultrasonic power of 200-300W for 30-60 minutes, and drying to obtain the surface-modified nano zinc oxide.
6. The method for preparing a juice packaging bottle according to claim 4 or 5, characterized in that: The injection molding temperature of depositing the nano-silver antibacterial coating on the surface of the LDPE liner in S4 is 180-200° C., and the injection molding pressure is 50-70 MPa.
7. The method for preparing a juice packaging bottle according to claim 4 or 5, characterized in that: The sealing test described in S5 adopts the pressure difference method, maintaining the pressure at 20kPa for 30s, and the pressure drop value is ≤5kPa; the additive migration amount detection adopts high performance liquid chromatography, and the detection conditions are: chromatographic column C18 (4.6mm×250mm, 5μm), mobile phase methanol-water, volume ratio 60:40, flow rate 1.0mL / min, detection wavelength 254nm.